The Influence Of Brand Awareness And Brand Image On Emina Product Purchase Decisions(Survey on Students in Tasikmalaya City): Yopilia Putri Pandan Wangi; H. Ari Arisman; Gian Riksa Wibawa - Wangi, Yopilia Putri Pandan; Arisman, H Ari; Wibawa, Gian Riksa (Innovative Business Management Journal, 2024)
This research aims to determine the influence of Brand Awareness and Brand Image on Emina Product Purchasing Decisions. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Brand Awareness and Brand Image simultaneously have a positive and significant effect on Purchasing Decisions. Brand Awareness partially has a significant effect on Purchasing Decisions. Brand Image partially has a significant effect on Purchasing Decisions.